The mediating role of competitive intelligence on organizational culture and hotel performance: a proposed theoretical framework / Dian Aszyanti Atirah Mohd. Asri, Ainul Mohsein Abdul Mohsin and Norzuwana Sumarjan - Mohd. Asri, Dian Aszyanti Atirah; Abdul Mohsin, Ainul Mohsein; Sumarjan, Norzuwana (Universiti Teknologi MARA, Perlis, 2022)
The tourism industry is widely acknowledged in modern economies. However, to remain competitive, hotels are encouraged to implement strategic planning. The primary goal of this study is to propose a theoretical framework that integrates the role of Competitive Intelligence (CI) in the relationship between organizational culture and hotel performance. Therefore, an in-depth study on CI practices in the hotel industry is needed. However, a lot of previous research has been conducted on CI in other industries, especially in the SME industry. Nonetheless, to the best of the researcher's knowledge, little is known about the role of Competitive Intelligence (CI) practices in the relationship between Organizational Culture (OC) and hotel performance in Malaysia. Therefore, the use of Resource-Based Theory and Knowledge-Based theory and their justifications among studies on CI is highlighted. A three-phased process to create this framework begins with a detailed explanation of the literature related to OC as a factor influencing hotel performance. Then, the framework inserts CI practices as a strategy to improve hotel performance. Finally, CI as a mediator between the relationship of OC and hotel performance is explained. This quantitative study uses a questionnaire survey of the top-level management of 240 Four and Five-star hotels obtained from the Ministry of Tourism, Arts, and Culture Malaysia and will be analyzed using PLS-SEM. This study adds to the growing body of CI literature and contributes to industry practitioners to better understand the factor and strategies to improve hotel performance.